Assesment of ROM scale with regards to variation in depth at landslide tragedic sites in Selangor/Tengku Firdaus Tuan Lah - Tuan Lah, Tengku Firdaus (Faculty of Civil Engineering, 2007)
In Malaysia, slope failure always occurs especially during the rainy seasons from October to January. Slope failure causes loss of life and damage to properties. Factors contributing to slope failure include soil types, steepness of slope, vegetative cover on slope, groundwater table rise, vibration and etc. In this study, two locations were identified namely slope failure at Bukit Antarabangsa, Selangor and Kampung Pasir Ulu Klang, Selangor. Soil samples were taken at 0m, 0.3m, 0.6m, and 0.9m depth both at failure and unfailed zones. Base on the ROM Scale, both the failed and unfailed slopes are in the category of high to critical risk. The unfailed slopes are still stable due to negative suction. Regardless, the long term stability of slope is either suspected.